Hot Deformation and Work Hardening Behavior of an Extruded Mg–Zn–Mn–Y Alloy. Issue 12 (December 2015) - Tahreen, N.; Zhang, D.F.; Pan, F.S.; Jiang, X.Q.; Li, D.Y.; Chen, D.L.
Abstract : The aim of this study was to evaluate the strain hardening and hot deformation behavior of as-extruded Mg–Zn–Mn (ZM31) magnesium alloy with varying Y contents (0.3, 3.2, and 6 wt%) via compression testing along the extrusion direction at room temperature, 200 °C and 300 °C. Texture and phases were identified by X-ray diffraction. Alloy ZM31 + 0.3Y consisted of a mixture of fine equiaxed grains and elongated grains with I-phase (Mg3 YZn6 ); alloy ZM31 + 3.2Y contained I-phase and W-phase (Mg3 Y2 Zn3 ); alloy ZM31 + 6Y had long-period stacking-ordered (LPSO) X-phase (Mg12 YZn) and Mg24 Y5 particles. With increasing Y content the basal texture became weakened significantly. While alloys ZM31 + 0.3Y and ZM31 + 3.2Y exhibited a skewed true stress–true stain curve with a three-stage strain hardening feature caused by the occurrence of { 10 1 ¯ 2 } extension twinning, the true stress–true stain curve of alloy ZM31 + 6Y was normal due to the dislocation slip during compression. With increasing temperature the extent of skewness decreased. While the compressive yield stress, ultimate compressive stress, strain hardening exponent, and hardening capacity all decreased as the temperature increased, the retention of the high-temperature deformation resistance increased with increasing Y content mainly due to the presence of thermally-stable LPSO X-phase.